Spatiotemporal Characteristics and Regional Variations of Active Fires in China since 2001 - Chenqin Lian; Chiwei Xiao; Zhiming Feng (Remote Sensing, 2022)
Currently, fires (e.g., biomass burning and/or straw burning) are still prevailing and serious globally. However, the issue of the characteristics, types, and drives of fire occurrence is always a challenge and varies distinctively worldwide. Using Moderate Resolution Imaging Spectroradiometer (MODIS) Collection 6 (C6) active fire products during 2001–2020, here, we analyzed the occurrence frequencies and spatiotemporal characteristics of active fires at the provincial and regional to national scales and at the monthly and annual scales in China. The accumulated occurrence frequencies of MODIS C6 active fires in China were up to 184.91 × 104 in the past two decades, and the average annual level was 9.25 × 104, especially in 2014 (15.20 × 104). The overall trend of active fires was rising and then falling, but with significant spatial and temporal differences in the last 20-years. Temporally, nearly 61% of active fires occurred in spring (36%) and autumn (25%), particularly in August (16%), April (14%), and October (13%). Spatially, about 90% of active fires occurred in the east of the Hu Huanyong Line, particularly in Northeast China (25%), South China (23%), and East China (20%). In China, the most active fires were concentrated in the Northeast Plain, the North China Plain, the southeast hills, and the Yunnan–Kweichow Plateau. In terms of temporal differences across regions, active fires in Northeast China, North China, and Northwest China were concentrated in spring and autumn, especially in March, April, and October; in East China, they were concentrated in summer, especially in June; and in South China and Southwest China, they were concentrated in winter and spring, especially from December to April of the following year. Our study provides a full analysis of spatio–temporal characteristics and changes of active fires in China, and it can also assist in supplying a beneficial reference for higher monitoring and controlling of fires such as straw burning.